Health Insurance and Access to Care among Welfare Leavers - Sheldon Danziger; Matthew M. Davis; Sean Orzol; Harold A. Pollack (SAGE Publishing, 2008)
This analysis explores the effects of the 1996 welfare reform on health insurance coverage and access to care among former recipients of cash aid. Using panel data from the Women's Employment Study, which conducted five interviews between 1997 and 2003 in one Michigan county, we find that 25% of welfare leavers lacked health insurance coverage in fall 2003. Uninsured adults were significantly more likely than others to report that they could not afford a medical or dental visit during the year prior to the 2003 interview. Fixed-effect logistic regression analysis indicates that women who had been off the welfare rolls for at least 12 months (the duration of transitional Medicaid) were significantly more likely to be uninsured than women who had made more recent welfare exits, and were significantly more likely to report financial obstacles to the receipt of medical and dental care.